TERTIARY PHOSPHINE ADDUCTS OF [W2(MU-O2CBU(T))4] - CRYSTAL-STRUCTURE OF [W2(MU-O2CBU(T))3(O2CBU(T)) (PME2PH)2] - Mountford, P; Williams, J (1993)
Treatment of the quadruply bonded ditungsten complex [W2(μ-O2CBut)4] with phosphines PMeRR′ (R = R′ = Me or Ph; R = Me, R′ = Ph) affords bis(adducts) which have the general formula W2(O2CBut)4·2PMeRR′. Each adduct possesses a different arrangement of the PMeRR′ and O2CBut ligands. The complex [W2(μ-O2CBut)2(O 2CBut)2(PMe3)2] contains two equatorially bound phosphine ligands per dimeric unit whereas in [W2(μ-O2CBut)4(PMePh 2)2] both phosphine ligands are axially co-ordinated. The crystallographically characterised complex [W2(μ-O2CBut)3(O 2CBut)(PMe2Ph)2] has a novel geometry in which one axially and one equatorially co-ordinated PMe2Ph ligand is present. The compound [W2(μ-O2CBut)2(O 2CBut)2(PMe3)2] reacts with carbon monoxide or chlorotrimethylsilane to afford mononuclear [W(O2CBut)2(CO)3(PMe 3)2] or dinuclear [W2(μ-O2CBut)2Cl 2(PMe3)2] respectively.